2012
DOI: 10.1007/s11746-012-2173-0
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Cyclolinopeptides: Analysis and Storage Stability

Abstract: Fourteen cyclolinopeptides (CLPs) from flaxseed oil and meal were separated, identified and quantified by HPLC coupled to an Orbitrap MS. The oxidative stability of the cyclolinopeptides was assessed during storage of flaxseed oil and meal. A significant decrease in the amounts of the methionine containing CLPs, namely CLP‐B, CLP‐J and CLP‐M, and a concurrent increase in the amounts of methionine sulfoxide containing CLPs, such as CLP‐C, CLP‐E and CLP‐G were observed. The cyclolinopeptides with two methionine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 24 publications
6
45
0
2
Order By: Relevance
“…The novelty of our latest HLPC method developed is in its ability to resolve nine naturally occurring flax orbitides (CLs 2, 3, 5, 6, 8, 10, 13, 14, and 17) in 2.5 min. Like Aladedunye et al [31], CL 1 co-eluted with CL 7 under our HPLC gradient.…”
Section: Faster Hplc Monitoring Offlinesupporting
confidence: 56%
See 1 more Smart Citation
“…The novelty of our latest HLPC method developed is in its ability to resolve nine naturally occurring flax orbitides (CLs 2, 3, 5, 6, 8, 10, 13, 14, and 17) in 2.5 min. Like Aladedunye et al [31], CL 1 co-eluted with CL 7 under our HPLC gradient.…”
Section: Faster Hplc Monitoring Offlinesupporting
confidence: 56%
“…Other authors [31] have reported separation of fourteen known naturally occurring CLs (not including 4, 9, and recently published 18, 19 and 20), but with 1 and 7 co-eluting, using a Kinetex C18 column (2.6 m; 150 mm × 3 mm; Phenomenex, MA). However, the length of their HPLC gradient was 45 min.…”
Section: Faster Hplc Monitoring Offlinementioning
confidence: 99%
“…This was, in part, in agreement with Bhatty (1993) who reported that the trypsin inhibitor levels differed between flax varieties but also found differences between the cyanogenic glycoside content of the same cultivars. In spite of its content of linolenic acid, flaxseed flour arising from cold pressing has excellent oxidative stability (Aladedunye, Sosinska, & Przybylski, 2013). When petroleum ether defatted flaxseed meal was mixed with commercially purchased flaxseed oil it was found that the antioxidant system of the meal confered stability to the oil (Barthet, Klensporf-Pawlik, & Przybylski, 2014).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…12 The absence of known flax orbitides 4 and 9 suggested that the flaxseed oil had not yet undergone extensive oxidation. 8,12,23,24 The remaining known flax orbitides 18 and 19 that were recently identified were not detected in this extract probably due to either their occurrence at low concentration and/or the extraction procedure. 11 In addition to the 16 known peptides detected, signals for novel cyclolinopeptides 21, 22, 23, 24, and 25 were also observed ( Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 85%